Hubungan antara Pengetahuan Tingkat Pendidikan dan Sikap Pedagang Tentang Pengelolaan Sampah Di Pasar Ikan TPI Pulau Baai Kota Bengkulu - Syahrizal Ahmad, Ahmad; Oktavidiati, Eva; Ramon, Agus; Afriyanto (Avicenna: Jurnal Ilmiah, 2025)
Background: Waste is described as materials or substances with no financial worth that are created by people or natural events and are no longer needed. It can be found as solid matter, fluids, or vapor. This research aimed to explore the link between the perceptions of traders and their attitudes regarding how waste is handled at the TPI Pulau Baai fish market, situated in the city of Bengkulu. Method: This research project was built upon an analytical study that involved observation. The cross-sectional strategy, in particular, was put into action. The research focused on a total of 150 traders operating within the Pulau Baai fish market. A group of 60 traders was carefully selected to participate in the research after doing the required computations. The chi-square test was used to conduct the statistical analysis for bivariate assessment. The results of the study reveal a connection between comprehension and how waste is managed at the TPI Pulau Baai fish market, as shown by a P-value of 0.4, which is less than the cutoff of 0.5. There is a clear connection between the amount of knowledge and waste management strategies used at the TPI Pulau Baai fish market, as indicated by a P-value of 0.3, which is less than the threshold of 0.5. The research also highlights a connection between understanding among the public and how waste is handled at the TPI Pulau Baai fish market, as shown by a P-value of 0.1, which is also less than 0.5. Conclusion: advised that those who took part in the study should improve how they handle waste at the TPI Pulau Baai fish market to keep the market space organized and free of disease-causing organisms. Keywords: Market, Knowledge, Education Level, Attitude